Fracture and Weakening of Jammed Subduction Shear Zones, Leading to the Generation of Slow Slip Events. (8th November 2019) - Beall, Adam; Fagereng, Åke; Ellis, Susan
Abstract: Geodetic data have revealed that parts of subduction interfaces creep steadily or transiently. Transient slow slip events (SSEs) are typically interpreted as aseismic frictional sliding. However, SSEs may also occur via mixed viscobrittle deformation, as observed in shear zones containing mixtures (mélange) of strong fractured clasts embedded in a weak viscobrittle matrix. We test the hypothesis that creep in a subduction mélange occurs through distributed matrix deformation, where flow is intermittently impeded by load‐bearing clast networks (jamming). Our numerical models demonstrate that bulk mélange rheology can be dominated by the strong clasts in the absence of fracturing, while at high driving stresses or low frictional strength, clast fracturing redistributes deformation into the matrix, leading to high bulk strain rates. Because mélange stress is heterogeneous, fracturing of clasts occurs throughout jammed mélange when the driving stresses are only ∼20 % of the clast yield strength. The effective rheology of jammed mélange can be characterized by a logarithmic dependence of stress on strain rate, which is used to explore strain rate transients caused by temporal variation in clast friction. Clasts must weaken significantly (∼75 % ) in order to increase strain rate by 8 times. Spring‐block slider models with a more idealized viscobrittle rheology also demonstrate that strain rate transients can be generated when rate‐and‐state friction is incorporated. We outline a model where high bulk strain rates are generated when pervasive fracturing occurs, but further slip is limited by viscous processes. Incorporating such viscous damping into models may widen the conditions under which SSEs can occur while preventing development of seismic slip. Plain Language Summary: While some subduction zones are responsible for generating large earthquakes, others creep steadily or episodically. This range of deformation styles may correspond to the interplay between viscous creep and frictional failure, as observed in exhumed subduction shear zones, which are typically mixtures (mélanges) of strong fractured and weak viscous materials. We use computer models to explore how mélange strength and deformation style varies when the frictional material fractures. Load‐bearing networks of unfractured strong material contribute significantly to mélange strength, so the onset of fracturing redistributes some deformation into the weak viscous material. As the force distribution in these networks is complicated, the onset of frictional failure alone is insufficient to completely unload the strong material. However, if the frictional material weakens considerably, mélange may undergo a period of rapid, predominately viscous deformation. Cycles of viscous deformation may correspond to episodic creep events. If creep events do occur primarily by a viscous mechanism, this may explain why they can occur routinely in some regions without transitioning to seismic slip. Key Points: Fracturing of strong clasts in a weak melange occurs at applied stresses 80% lower than for a homogeneous fault Fracturing of clasts in load‐bearing force chains leads to stress redistribution into the viscously creeping matrix Clast strength must be reduced significantly in order to generate transient slip, depending on the degree of melange jamming